The Impacts of EU Support Programs on SMEs: A Literature Review (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
The role of Small and Medium-sized enterprises (SMEs) as a source of employment opportunities and innovation in our local and regional territories is well known. However, the SMEs must face different challenges due to the dynamic context in which they are operating and the global competition. In this direction public policies are trying to support the SMEs competitiveness and innovation, through different instruments and programmes managed at national and regional level or thematic funding opportunities. In this context, several studies focused on monitoring the impacts of public support programs on turnover, investments and innovation activities in SMEs have been conducted, showing as there are general positive effects for the SMEs participating in these programs. The contribution of this paper is to identify the existing literature on the impacts of the financial support programs on SMEs, analysing the contribution of practitioners and academics and empirical researches. Literature available from 2002 to the present have been analysed using Web of Science and Scopus and using the databases available on European Commission website. Preliminary findings have shown as there is the need of a deeper investigation about the participation in EU programmes and the main contributions derive from the researchers conducted by practitioners.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.